Pemberdayaan Usaha Rumahan melalui Pelatihan AI Marketing - Adhi Prakosa; Arif Sudaryana; Galuh Mira Saktiana (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2025)
Artificial intelligence (AI) technology, when used by small and medium-sized businesses, can have a significant impact on them. This community service project provided workshops in Gandekan to help the community maximise digital marketing with AI. The workshop was held in the tourist village of Dewi Gumi with 35 participants. At the end of the workshop, the findings showed an increase in understanding and skills in digital marketing content creation.